Interaction of mitochondrial formylated peptides with formyl peptide receptor 1 in the pathogenesis of acute lung injury. (25th February 2016) - Dorward, David; Lucas, Christopher; Doherty, Mary; Chapman, Gavin; Scholefield, Emma; Conway-Morris, Andrew; Kipari, Tiina; Robb, Calum; Felton, Jennifer; Whitfield, Philip; Haslett, Christopher; Dhaliwal, Kevin; et al.
Abstract: Background: Mortality in acute respiratory distress syndrome remains high with no effective pharmacological therapies. The syndrome is characterised by dysregulated neutrophilic inflammation and tissue damage, which leads to the release of various factors including mitochondrial formylated peptides to drive neutrophil migration to sites of inflammation. This study investigated the importance of mitochondrial formylated peptides and their interaction with formyl peptide receptor 1 (FPR1) in the pathogenesis of acute lung injury. Methods: Formylated peptides were identified in bronchoalveolar lavage fluid (BALF) from patients with acute respiratory distress syndrome and healthy controls by liquid chromatography-tandem mass spectrometry. Intratracheal hydrochloric acid (pH 2) was instilled in wild-type (WT) and FPR1 –/– mice, and BALF neutrophils, cytokines, and protein were quantified at 24 h. WT mice received the FPR1 antagonist cyclosporin 12 h after injury. In-vitro experiments used neutrophils from healthy human blood to assess neutrophil responses to formylated peptides. Data were analysed by t testing and ANOVA. The study was approved by Lothian Research Ethics Committee. Findings: Formylated peptides were present in patients with acute respiratory distress syndrome (n=11) but were undetectable in healthy controls (n=10). FPR1–/– mice (n=8) had reduced concentration of BALF neutrophils compared with WT mice (n=10) (49 per μL BALF [SD 48] vs 160 [93], p=0·02), less cytokine release (tumour necrosis factor α 146 pg/mL [46] vs 242 [94], p=0·03), and less protein leak (IgM 282 ng/mL [190] vs 678 [616], p=0·04). Cyclosporin H similarly reduced lung inflammation. After identification of FPR1 on type 1 alveolar epithelial cells, bone marrow chimeras confirmed that both myeloid and non-myeloid cell FPR1 contributed to alveolar protein leak during lung injury. In-vitro studies revealed that mitochondrial formylated peptides induced neutrophil responses through intracellular MAPK/PI3K signalling and upregulation of β2-integrin heterodimer macrophage-1 antigen. Interpretation: This study demonstrated that mitochondrial formylated peptides are present in acute respiratory distress syndrome and that FPR1 inhibition, or absence, reduces lung injury through neutrophil-dependent and neutrophil-independent means. Although our study combined samples from patients with those of a clinically relevant model, we used only one method of inducing lung injury, unlike that seen in acute respiratory distress syndrome. Importantly, however, FPR1 antagonists delivered after injury reduced lung inflammation suggesting a potential therapeutic role. Funding: Wellcome Trust, Medical Research Council.